Taxation economics and the tax reform for acceleration and inclusion law (TRAIN LAW) - Montemayor, Jose C. Jr. (Quezon City, Philippines : Central Book Supply, 2018)
The book contains the governing laws and analysis of TRAIN LAW. Also included in the appendix the Republic Act No. 10963 otherwise tagged as the Tax Reform for Acceleration and Inclusion Act or TRAIN introduces omnibus amendments to the current National Internal Revenue Code (NIRC) or Tax Code effective January 1, 2018.
Foreword -- Contents -- TRAIN LAW (Taxation Economics and the Tax Reform for Acceleration and Inclusion Law) -- APPENDIX - REPUBLIC ACT NO. 10963 - Tax Reform for Acceleration and Inclusion (TRAIN) ACT.
Keywords: TAXATION -- LAW AND LEGISLATION -- PHILIPPINES